2014
DOI: 10.1007/978-3-319-04843-7_3
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Tyrosine Kinases in Osteosarcoma: Not Just the Usual Suspects

Abstract: Despite aggressive surgical and chemotherapy protocols, survival rates for osteosarcoma patients have not improved over the last 30 years. Therefore, novel therapeutic agents are needed. Receptor tyrosine kinases have emerged as targets for the development of new cancer therapies since their activation leads to enhanced proliferation, survival, and metastasis. In fact, aberrant expression and activation of RTKs have been associated with the progression of many cancers. Studies from our lab using phosphoproteom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 133 publications
0
28
0
Order By: Relevance
“…Over-expression, found in the majority of malignant pleural mesothelioma specimens, was shown to influence patient survival, independently of other established prognostic factors [74]. Axl has been proposed as a therapeutic target also in osteosarcoma, being among the most frequently activated RTK [75]. In keeping with this evidence, Gas6/Axl have been reported to inhibit apoptosis and to promote migration and invasion of osteosarcoma cells [76].…”
Section: Regulation Of Cell Survivalmentioning
confidence: 81%
See 1 more Smart Citation
“…Over-expression, found in the majority of malignant pleural mesothelioma specimens, was shown to influence patient survival, independently of other established prognostic factors [74]. Axl has been proposed as a therapeutic target also in osteosarcoma, being among the most frequently activated RTK [75]. In keeping with this evidence, Gas6/Axl have been reported to inhibit apoptosis and to promote migration and invasion of osteosarcoma cells [76].…”
Section: Regulation Of Cell Survivalmentioning
confidence: 81%
“…Lung [41,45,49,82,83,84,88,90,91] Breast [55,80,103] Colon [47,57] Liver [44] Pancreas [60] Kidney [39] Melanoma [77][78][79] Cutaneous squamous cell cancer [56] Glioblastoma [48,63,66] Ovarian [68,69] Prostate [70] Esophageal squamous cell [87] Head and neck [81,87] Mesothelioma [72][73][74] Osteosarcoma [75,76] Gastrintestinal stromal (GIST) [8] Myeloid leukemia [9] Acute myeloid leukemia [89] Chronic myeloid leukemia [97] Chronic lymphocytic leukemia B cells [101] 1 The tumor subtypes mentioned in the review are reported. Gas6 is mentioned in Ref.…”
Section: Tumor Type Referencesmentioning
confidence: 99%
“…In the same manner, another study showed that knockdown of Axl increased apoptosis and decreased proliferation, also mediated by downregulation of the Akt pathway [ 97 ]. A recent study unraveled additional RTKs involved in the metastatic potential of osteosarcoma, and after lengthy metastatic-dependent validations Axl came out as a top hit in a metastatic osteosarcoma cell line [ 98 ]. Axl also emerged from another screen for differentially expressed genes in high versus low metastatic osteosarcoma sublines [ 99 ].…”
Section: Tissue and Cell Type-specific Roles For Axlmentioning
confidence: 99%
“…Although investigated by numerous previous studies, the molecular mechanisms of the etiology and pathogenesis underlying OS remain to be elucidated (19,20). Therefore developing effective therapeutic strategies for the treatment of OS is challenging.…”
Section: Discussionmentioning
confidence: 99%